PENGARUH MANAJEMEN STRATEGI DAN PENYUSUNAN ANGGARAN HIBAH PEMILIHAN TERHADAP KINERJA KOMISI PEMILIHAN UMUM KABUPATEN LAMPUNG TENGAH - Rifky Febrihanuddin Azis (Universitas Muhammadiyah Lampung, 2023)
The General Election Commission (KPU) is a non-structural state institution that provides public services in the field of holding elections and elections. In planning its duties and functions, the KPU of Central Lampung Regency has prepared strategic plans, annual work plans and performance agreements. Implementation of strategic management and preparation of the budget are considered to affect institutional performance, both financial performance and program activities. This research is a descriptive research with a correlational quantitative approach. The variables tested in this study are the implementation of strategic management and budgeting as independent variables and performance achievement as the dependent variable. This study uses secondary data in the form of institutional documents in the form of comments on strategic plans, annual work plans, performance reports and budget realization. This study shows that the variable (X1) is the application of strategic management which moves towards improving election performance. Variable (X2) the implementation of budgeting that affects institutional performance.